A summation‐integral type modification of Szász–Mirakjan operators. (27th May 2016) - Mishra, Vishnu Narayan; Gandhi, R. B.
Abstract : In this paper, we introduced a summation‐integral type modification of Szász–Mirakjan operators. Calculation of moments, density in some space, a direct result and a Voronvskaja‐type result, are obtained. Copyright © 2016 John Wiley & Sons, Ltd.